Treatment of Tuberculosis Infection in Children - Cruz, Andrea T. (Journal of Pediatric Infectious Diseases, 2018)
The last decade has seen publication of more robust data for shorter course regimens for tuberculosis infection. These regimens are associated with higher completion rates than the traditional 6- to 9-month course of daily isoniazid (INH). These shorter regimens include 4 months of daily rifampin (RIF) and 12 once-weekly doses of INH and a long-acting rifamycin and rifapentine. In addition, a widely used regimen in the United Kingdom is 3 or 4 months of daily INH and RIF. All regimens have demonstrated efficacy in the ideal conditions of clinical studies, and all have very low rates of hepatotoxicity in children. These newer regimens likely are more effective than longer courses of INH once patient and family adherence is considered. Clinicians need to be cognizant of poor completion rates with traditional INH therapy and how the use of rifamycin-containing regimens offers more palatable options for children and their families.
Keywords: isoniazid; pediatric; rifapentine; short-course preventive therapy; tuberculosis infection